The francoism against the wall. Poetics and citizenship in the graffiti of the spanish transition - Labrador Méndez, Germán (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper proposes a study from critical theory and cultural studies of a study of the graffiti made in the seventies on the walls of Spanish cities against the Franco dictatorship.
Keywords: critical theory; cultural studies; graffiti; francoism; spanish transition